Documenting the 'soft spaces' of London planning: Opportunity Areas as institutional fix in a growth-oriented city. Issue 3 (4th March 2022) - Ferm, Jessica; Freire Trigo, Sonia; Moore-Cherry, Niamh
ABSTRACT: The concentration of economic growth into large metropolises is widely documented across Europe. Yet, planning of this growth at the strategic metropolitan scale shows significant variation. This paper documents the evolution of Opportunity Areas within Greater London. Through statistical and documentary analysis, and participant observation, we reveal how they have been repurposed from a tool employed to facilitate brownfield regeneration to one that sustains growth through brokering relationships, enhancing land value and capturing it. The paper argues that the cumulative impact of these 'soft spaces' of planning represents a fundamental change in the nature of strategic planning for city-regions.